COMPETITION AND RATCHET HYPOTHESIS: HOW SAFE ARE MANUFACTURING COMPANIES IN SUB-SAHARAN AFRICA? (Malaysian Management Journal, 2021)
This study applied the conventional ratcheting notion that managers (agents) chose to restrict their performance because they anticipated that firms (principals) would respond to higher performance levels by raising targets or by cutting pay in a piece-rate labour environment. A cross-sectional panel model was developed to subject this baseline notion of ratcheting hypothesis to multi-period and ex-post competitive labour market environment, bearing in mind that there was information asymmetry to both parties. It was observed, as predicted by the theoretical model that there would be substantial ratchet effects in the absence of competition. However, when subjected to ex-post competition, the ratchet effects were reduced, regardless of whether market conditions favoured the firms or the managers and thereby making the manufacturing companies in Sub-Saharan Africa safer than when they were exposed to ratcheting in its conventional form.